The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2169/internalmedicine.55.6872
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Infliximab Therapy and Methotrexate Monotherapy to Improve the Clinical Effect in Rheumatoid Arthritis Patients

Abstract: Objective We examined whether infliximab (IFX) therapy was more effective than methotrexate (MTX) monotherapy to achieve an improvement in depressive states in Rheumatoid Arthritis (RA) patients. Methods We examined 152 RA patients (72 IFX patients and 80 MTX patients).We conducted an openlabel cohort study to evaluate the disease activity of RA (Simplified Disease Activity Index; SDAI), depressive states (Hamilton Rating Scale for Depression; HAM-D), Activity of Daily Living (ADL) (modified Health Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…RA is treated with conventional synthetic (cs) disease-modifying anti-rheumatic drugs (DMARDs), biologic (b) DMARDs, targeted synthetic (ts) DMARDs and glucocorticoids [8]. An open-label cohort study found that bDMARDs improve depression in RA patients [75]. Another prospective single-blinded study reported that csDMARDs and bDMARDs have a similar effect on improving depressive symptoms in RA patients [76].…”
Section: Ra Therapies: Impacts On Fatigue Depression and Cognitionmentioning
confidence: 99%
“…RA is treated with conventional synthetic (cs) disease-modifying anti-rheumatic drugs (DMARDs), biologic (b) DMARDs, targeted synthetic (ts) DMARDs and glucocorticoids [8]. An open-label cohort study found that bDMARDs improve depression in RA patients [75]. Another prospective single-blinded study reported that csDMARDs and bDMARDs have a similar effect on improving depressive symptoms in RA patients [76].…”
Section: Ra Therapies: Impacts On Fatigue Depression and Cognitionmentioning
confidence: 99%
“…We analyzed ( 1 ) the differences in background characteristics due to the presence or absence of depression ( 2 ), the correlation coefficients between HAM-D and the other factors ( 3 ), the correlation coefficients between the serum OXT levels and other factors, and ( 4 ) the serum OXT levels before and after bDMARD treatment. The following statistical analyses were performed: a Mann-Whitney U test, chi-squared test, Pearson's moment correlation coefficient and a repeated-measure analysis of variance (ANOVA).…”
Section: Methodsmentioning
confidence: 99%
“…The odds ratio for depression in RA patients was 1.42 (95% confidence interval (CI): 1.3, 1.5; relative to healthy individuals) ( 2 ). The treatment of RA with biological disease-modifying antirheumatic drugs (bDMARDs) is known to be highly effective in reducing the disease activity as well as the severity of depression that occurs in association with RA ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative study of monoteraphy of methotrexate vs. infliximab showed that both groups of patients taking one or the other drug had a lower likelihood of depression. Given the Hamilton Rating Scale for Depression (HAM-D) and Disease Activity Score (DAS), there was no statistical difference between them [31,32], and on the Self-Rating Depression Scale (SDS) there was a statistical difference between them in favor of infliximab [32]. However, in RA therapy alone, imfliximab was significantly more effective than monotrexate alone [31].…”
Section: Imfliximabmentioning
confidence: 99%